2022
DOI: 10.3389/fpsyg.2022.897896
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Insomnia of Front-Line Medical Staff During the COVID-19 Outbreak in China: An On-Line Cross-Sectional Study

Abstract: PurposeDuring the COVID-19 outbreak, medical staff working in high-risk workplaces had a higher rate of epidemic infection. They also faced heavy workloads and pressure, which means they are more likely to suffer from psychological problems than others. To understand the mental health of medical staff during the epidemic, we explore the characteristics of medical staff susceptible to negative psychological emotions during the outbreak of public safety and health events. At the same time, we provide correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In China, the incidences of anxiety, depression, and insomnia among the frontline healthcare providers who were long-term working in square cabin hospitals ranged from 25% to 58%, 29% to 54%, and 34% to 36%, respectively. These mental health problems are much more serious than non-frontline healthcare workers (Zhang et al, 2022). Studies have shown progressively higher anxiety levels in frontline healthcare workers over time, with heavy nursing tasks, risk of infection, and isolation as common risk factors (Luo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the incidences of anxiety, depression, and insomnia among the frontline healthcare providers who were long-term working in square cabin hospitals ranged from 25% to 58%, 29% to 54%, and 34% to 36%, respectively. These mental health problems are much more serious than non-frontline healthcare workers (Zhang et al, 2022). Studies have shown progressively higher anxiety levels in frontline healthcare workers over time, with heavy nursing tasks, risk of infection, and isolation as common risk factors (Luo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 61 pointed out that compared with nonmedical workers, medical workers, especially those with organic diseases, had a higher prevalence of COVIDRI, anxiety, depression and obsessive-compulsive symptoms during the pandemic in China. Zhang et al 62 surveyed the impact of the COVID-19 pandemic on medical workers in tertiary hospitals in China and showed that 53.37% of healthcare workers suffered from COVIDRI symptoms. Compared with those who had received higher education, healthcare workers with lower educational backgrounds had higher levels of COVIDRI.…”
Section: Special Populations With Covidrimentioning
confidence: 99%